RETRACTED: Formation of a competitive specialist based on the introduction of a competence-based approach in education - Vartanova Natalia; Kuzminova Irina; Lin Lan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001